Complement component 1, q subcomponent binding protein is a marker for proliferation in breast cancer - Jane Scully, Olivia (Exp Biol Med (Maywood), 2015)
Complement component 1, q subcomponent binding protein (C1QBP), is a multi-compartmental protein with higher mRNA expression reported in breast cancer tissues. This study evaluated the association between immunohistochemical expression of the C1QBP protein in breast cancer tissue microarrays (TMAs) and clinicopathological parameters, in particular tumor size. In addition, an in vitro study was conducted to substantiate the breast cancer TMA findings. Breast cancer TMAs were constructed from pathological specimens of patients diagnosed with invasive ductal carcinoma. C1QBP protein and proliferating cell nuclear antigen (PCNA) immunohistochemical analyses were subsequently performed in the TMAs. C1QBP immunostaining was detected in 131 out of 132 samples examined. The C1QBP protein was predominantly localized in the cytoplasm of the breast cancer cells. Univariate analysis revealed that a higher C1QBP protein expression was significantly associated with older patients (P = 0.001) and increased tumor size (P = 0.002). Multivariate analysis showed that C1QBP is an independent predictor of tumor size in progesterone-positive tumors. Furthermore, C1QBP was also significantly correlated with expression of PCNA, a known marker of proliferation. Inhibition of C1QBP expression was performed by transfecting C1QBP siRNA into T47D breast cancer cells, a progesterone receptor-positive breast cancer cell line. C1QBP gene expression was analyzed by real-time RT-PCR, and protein expression by Western blot. Cell proliferation assays were also performed by commercially available assays. Down-regulation of C1QBP expression significantly decreased cell proliferation and growth in T47D cells. Taken together, our findings suggest that the C1QBP protein could be a potential proliferative marker in breast cancer.